Archeologia o przeszłości Poznania i jego zaplecza : stan i potrzeby badań - Kaczmarek, Jarmiła; Kaczmarek, Hieronim (Poznań : Muzeum Archeologiczne w Poznaniu, 2013)
Summaries
Zbornik radova
Na spor. nasl. str.: Archaeological studies on the past of Poznań and its environs : the state of research and future perspective
Bibliografija iza svakog rada i uz tekst
Summaries in English.
Keywords: Poljska; Poznań; arheološka istraživanja; arheologija - teorija; arheologija okoliša